Unraveling the gut: the pivotal role of intestinal mechanisms in Kawasaki disease pathogenesis - Enfu Tao; Dandan Lang (Frontiers in Immunology)
Kawasaki disease (KD), an acute systemic vasculitis that primarily affects children under 5 years of age, is the leading cause of acquired heart disease in this age group. Recent studies propose a novel perspective on KD’s etiology, emphasizing the gastrointestinal (GI) tract, particularly the role of gut permeability. This review delves into how disruptions in gut barrier function trigger systemic inflammatory responses, exacerbate vascular inflammation, and contribute to coronary artery aneurysms. Evidence suggests that children with KD often exhibit increased gut permeability, leading to an imbalance in gut immunity and subsequent gut barrier damage. These changes impact vascular endothelial cells, promoting platelet aggregation and activation, thereby advancing severe vascular complications, including aneurysms. Additionally, this review highlights the correlation between GI symptoms and increased resistance to standard treatments like intravenous immunoglobulin (IVIG), indicating that GI involvement may predict therapeutic outcomes. Advocating for a new paradigm, this review calls for integrated research across gastroenterology, immunology, and cardiology to examine KD through the lens of GI health. The goal is to develop innovative therapeutic interventions targeting the intestinal barrier, potentially revolutionizing KD management and significantly improving patient outcomes.